Subnational Debt, Insolvency, and Market Development - Canuto, Otaviano (World Bank, Washington, DC, 2014)
State and local debt and the debt of quasi-public agencies have grown in importance as a result of fiscal decentralization, rapid urbanization, and the increasing role played by private capital. However, with debt comes the risk of insolvency. This note outlines a set of aligned fiscal incentives that should be in place, as well as the design issues to be considered in debt restructuring frameworks. This note also suggests some broad lessons extracted from several country experiences with subnational debt restructuring, insolvency frameworks, and debt market development. This note suggest a range of possible lessons to consider when designing reforms to align fiscal incentives and develop a robust subnational debt framework that can be used to effectively manage the insolvency risks that will inevitably accompany the new dynamism of subnational finance.